The Role of Rivaroxaban in a Comprehensive Protection Strategy for Patients with Atrial Fibrillation - I. A. Zolotovskaya; V. D. Sabanova; I. L. Davydkin (Столичная издательская компания, 2021)
Anticoagulant therapy of patients with atrial fibrillation is an integral part of their treatment strategy. The high risk of developing a cardioembolic stroke and the high comorbidity of this group of patients necessitates a comprehensive approach to treatment, taking into account all available risk factors. Atrial fibrillation is often asymptomatic and timely detection of these patients can be one of the most important tasks in the complex of measures aimed at protecting patients from stroke. The European Society of Cardiology's 2020 guidelines suggest the use of a CC to ABC patient management strategy. This strategy involves a number of measures aimed at managing atrial fibrillation, including confirming the diagnosis, determining the characteristics of atrial fibrillation and treatment tactics. One of the points of this strategy is the control of comorbidities and risk factors for cardiovascular diseases. To date, rivaroxaban has a number of convincing and reliable data on a high profile of efficacy and safety in the treatment of comorbid patients who not only have a high risk of stroke, but also need protection from coronary events and decreased renal filtration function. These data are confirmed by both the results of randomized clinical trials and data from real clinical practice. The review discusses the literature data describing the condition of patients with atrial fibrillation while taking direct oral anticoagulants, according to the search query "Atrial fibrillation, effectiveness and safety of rivaroxaban, warfarin, comorbidity, atrial fibrillation, efficacy and safety of rivaroxaban, warfarin, comorbid status" for the period from 2010 to 2020 in open sources PubMed and e-library, and a strategy for the comprehensive protection of patients with atrial fibrillation when using rivaroxaban is proposed for consideration.